From dreams to reality : market forces and changes from occupational intention to occupational choice - Jaik, Katharina [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2019)
"We empirically investigate whether the relationship between the fraction of filled apprenticeships in a particular occupation in the past and the fraction of prospective apprentices having very early intentions to train in this occupation has an impact on the decision to change the intended choice of occupation. We use a unique dataset from Switzerland containing detailed information on students’ early occupational 'dreams' (ages 13-14), before they undergo intensive career counselling, and combine it with information on their ultimate choice of occupation at the end of compulsory schooling (ages 15-16). The estimation results show that although the majority of students revise their initial intentions, those students who dreamed of learning an occupation with more training positions filled in previous years than peers interested in learning this occupation have a significantly higher probability of sticking to their initial dream occupation. Conversely, students who wished to train in an overly popular occupation have a higher probability of delaying the transition to upper-secondary education for at least one year, instead of switching to another occupation. In addition, we find on an aggregated level that a favourable situation on the apprenticeship market ultimately increases the premature contract termination rate due to a person-occupation-mismatch." (Authors' abstract, BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 2.1 Schulabgänger; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; L 5 Beratung & Orientierung; I 2.2.1 Westeuropa; Jugendlicher; Schulabgänger; Ausbildungsberuf; Berufserwartung; Berufswunsch; Berufswahl; Empirische Untersuchung; Regressionsanalyse; Schweiz